Meta‐analysis of the human gut microbiome from urbanized and pre‐agricultural populations. (28th February 2017) - Mancabelli, Leonardo; Milani, Christian; Lugli, Gabriele Andrea; Turroni, Francesca; Ferrario, Chiara; van Sinderen, Douwe; Ventura, Marco
Summary: Metagenomic studies of the human gut microbiome have only recently begun to explore the differences in taxonomic composition between subjects from diverse geographical origins. Here, we compared taxonomy, resistome and functional metabolic properties of publicly available shotgun datasets of human fecal samples collected from different geographical regions (Europe, North America, Asia and Oceania). Such datasets encompassed gut microbiota information corresponding to 13 developed/industrialized societies, as well as two traditional hunter‐gatherer, pre‐agricultural communities (Tanzanian and Peruvian individuals). Assessment of the retrieved taxonomic profiles allowed the most updated reconstruction of the global core‐microbiome as based on currently available data, as well as the identification and targeted genome reconstruction of bacterial taxa that appear to have been lost and/or acquired during urbanization/industrialization. Functional characterization of these metagenomic datasets indicates that the urbanization/industrialization process which occurred in recent human history has shaped the gut microbiota through the acquisition and/or loss of specific gut microbes, thereby potentially impacting on the overall functionality of the gut microbiome.